Volume 6: Oil and Gas Applications; Concentrating Solar Power Plants; Steam Turbines; Wind Energy 2012
DOI: 10.1115/gt2012-69075
|View full text |Cite
|
Sign up to set email alerts
|

The Physics of H-Darrieus Turbines Self-Starting Capability: Flapping-Wing Perspective

Abstract: It has been widely reported that Darrieus turbines cannot self-start and that they require external assistance to accelerate to their operating tip speed ratios. However, recent experiments have shown conclusively that H-Darrieus rotors with fixed-pitch blades that employ a symmetrical aerofoil can reliably self-start in steady controlled environments. Previous attempts have also been made to model the starting characteristics but there still exists a significant discrepancy between the experimental data and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Though clearly these results depend on the choice of aerofoil for the turbine. Woransinchai [8] observed that many of the early Darrieus turbines were constructed with low c/D ratios and the lack of unsteady thrust explains their inability to self-start.…”
Section: Effects Of Rotor Geometrymentioning
confidence: 99%
See 4 more Smart Citations
“…Though clearly these results depend on the choice of aerofoil for the turbine. Woransinchai [8] observed that many of the early Darrieus turbines were constructed with low c/D ratios and the lack of unsteady thrust explains their inability to self-start.…”
Section: Effects Of Rotor Geometrymentioning
confidence: 99%
“…However the curve is not perfectly sinusoidal suggesting that the motion can be decomposed into further components and not only pitch. The decomposition into pitch and plunge angles was described in detail by [8] and is shown in Fig. 5.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations